THE IMPORTANCE OF THE CLASSES OF SCHOOL PHYSICAL EDUCATION IN THE PROCESS OF SCHOOL INCLUSION FOR THE BEARERS OF SYNDROME OF DOWN. (Fiep Bulletin - online, 2015)
The objective of this work is to verify the importance of the classes of school physical education close to as school inclusion instrument the bearers of Syndrome of Down. The Syndrome of Down is due to a genetic alteration happened during or immediately after the conception. The genetic alteration is characterized more by the presence of the auto some 21, in other words, instead of the individual to present two chromosomes 21, it possesses three. It is her alteration denominated simple trisomy. The work elapses in the causes of the syndrome, in the development, the benefits of the school physical education as inclusion instrument, in the problems faced by that public, and the fearsome" prejudice." The research focuses the importance of the understanding of all so that the inclusion work elapses in a simple and satisfactory way. Some are presented suggestions to the teacher-educator, above all that still incipient, so that better they can attend those people bearers of deficiencies - that carry the syndrome of Down.
Keywords: Inclusion; down Syndrome; School physical education.